Pozaekonomiczne aspekty likwidacji szkół w gminach wiejskich - Kotarba, Bogusław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Niekorzystne trendy demograficzne w połączeniu z przyjętym sposobem finansowania wydatków oświatowych coraz częściej zmuszają władze gmin, zwłaszcza wiejskich, do likwidacji szkół z przyczyn ekonomicznych. Likwidacja szkoły ma jednak również inne, społeczne wymiary. W artykule na podstawie badań empirycznych przedstawiono ich analizę. Pozytywnie zweryfikowano hipotezę: pozaekonomiczne aspekty likwidacji szkół nie odgrywają większej roli w dłuższym okresie, nie powodują znaczącego spadku poparcia społecznego dla wójtów i burmistrzów i dlatego nie stanowią zagrożenia ich interesów politycznych.

Unfavorable demographic trends combined with the way educational expenditures are financed force commune authorities, especially rural ones, to close down schools for economic reasons more and more frequently. Apart from a financial one, a closure of a school has other, social dimensions as well. In the article, based on empirical studies, the analysis of those dimension is presented. The hypothesis that the non-economic aspects of school closure do not play a greater role in the long run, do not significantly reduce social support for commune heads and mayors and therefore do not pose a threat to their political interests has been positively verified.
Non-Economic Aspects of School Closures in Rural Communes
Keywords: gmina wiejska; oświata; likwidacja szkół; skutki społeczne; interes polityczny; rural community; education; school closure; social impact; political interest